Tingkat Pendidikan Pengusaha Dan Kinerja Usaha Bisnis Industri Mikro Kecil DKI Jakarta - Abdul Harif Siswanto; Nurul Hania (Pusat Studi Ekonomi Publikasi Ilmiah dan Pengembangan SDM, 2026)
Micro and Small Enterprises (MSEs), as productive economic activities, play a strategic role in expanding employment opportunities, increasing household incomes, and contributing to national foreign exchange earnings. However, most MSEs continue to face various challenges, particularly limited access to capital, difficulties in procuring raw materials, and restricted market access. These challenges are partly attributed to entrepreneurs’ limited knowledge, technical skills, and entrepreneurial attitudes. This condition highlights the importance of improving human resource quality, particularly through education. This study aims to analyze the effect of entrepreneurs’ educational attainment on the business performance of MSEs in DKI Jakarta Province. The study uses data from the 2024 survey conducted by Statistics Indonesia (BPS) on the Profile of Micro and Small Industries in DKI Jakarta, which was publicly disseminated through digital media. The results of linear regression analysis indicate that entrepreneurs’ educational attainment has a significant and positive effect on business performance. The regression equation, Y = 265,367,295.243 + 130,766.574X, indicates that higher educational attainment contributes to improved MSE business performance.